Soar Analysis on Marketing Strategy Integrated Online Smart Parking System - I Gede Susrama Mas Diyasa; Sugeng Purwanto; Wahyu S.J. Saputra; Slamet Winardi (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This research was conducted in transportation service industry of PT. Wastu Kencana in collaboration with UPN Veteran East Java through the Matching Fund program by Building an Integrated Online Smart Parking System (IOS-Park) Management Startup in 2022. Thus, this study needs to examine applying SOAR analysis to marketing strategies in this case study. Design/methodology/approach: The analysis method used in this study is a descriptive method with a qualitative approach, the data used is information about marketing strategies by interviews and observation Findings: The results showed that the management of this IOS Parking System start-up has many positive potentials that become strengths and business opportunities from internal and external. Practical implications: The results of this study are expected to be input and reference for the company in setting a selling strategy in the next sales period. Originality/value: This paper is original Paper type: a Research Paper